Women, Art and Wartime Industries: A Feminist Inter/Modern Analysis. Issue 101 (3rd July 2019) - Speck, Catherine
ABSTRACT: This article interrogates the gendered nature of modernism via analysis of the art work of two modern women painters, the American Edna Reindel and the Australian Sybil Craig. Each portrayed women working in shipbuilding, aircraft and munitions factories during the Second World War. While their paintings of women at work could be seen as complicit in the hegemonic masculinist political regimes which considered women a reserve army of labour, a feminist inter/modern reading runs counter to the conventional view that the masculinity of modern times was barely disturbed by women stepping into unusual roles under exceptional circumstances.